Can pyridostigmine improve lower urinary tract symptoms and bladder function in patients with potentially-weak bladder contractility? - Essa, Ahmed A. (International Journal of Psychosocial Rehabilitation, 2020)
Materials and methods A total of 60 patients with high urinary bladder volumes and significant urinary symptoms were included in this study. Patients were considered to have weak detrusor contractility (potentially suitable for pyridostigmine therapy) if they had clinical history of poor stream and/or subjective feeling of incomplete bladder emptying, confirmed by significant post-void residual urine (PVR) on ultrasound (Mindray DC30 hospital type), in the absence of            clinically           significant            mechanical            bladder                outflow       tract obstruction. Patients included were older patients with high bladder capacity and high PVR with persistent obstructive-like symptoms, such as females with high PVR with no urethral stricture or pelvic organ prolapse and males with high PVR on alpha blockers or those who failed to void after TURP and prostatectomy or did not show satisfactory symptomatic               improvement      or                        decrease                 in                          PVR                   after                     surgery. Baseline bladder volumes, both pre-void and post-void, were recorded and the measurements were repeated after 2 weeks of oral pyridostigmine 60 mg 3 times per day. Ultrasound measurements were obtained by a single experienced operator.Those attending urological clinic in Al-Noman Teaching Hospital and Privet clinic.A written consent was obtained from all patients participating in this study after explaining to them the important and purpose of the study, emphasized that such study could not harm them, with ensure them about complete confidentiality of information sought and will not be used other than research purpose. Patients were provided with a direct phone number to call in case of any bothersome adverse effects during pyridostigmine therapy.Results A total of 60 patients aged 40 to 65 years (mean 61.1 years, 41.7% females) included in this study, there was a significant overall decrease in PVR and significant improvement in voiding symptoms after 2 weeks of pyridostigmine therapy (mean PVR before treatment, 290.23± cc…and after treatment, 81.1±c ..p